Patients with obstructive sleep apnea can favor the predisposing factors of periodontitis by the presence of P. melaninogenica and C. albicans, increasing the severity of the periodontal disease - Téllez-Corral, Mayra A.; Herrera-Daza, Eddy; Cuervo-Jimenez, Hayde K.; Arango-Jimenez, Natalia; Morales-Vera, Darena Z.; Velosa-Porras, Juliana; Latorre-Uriza, Catalina; Escobar-Arregoces, Francina M.; Hidalgo-Martinez, Patricia; Cortés, Maria E.; Roa-Molina, Nelly S.; Otero, Liliana; et al. (Frontiers in Cellular and Infection Microbiology, 2022)
Objective The aim of this study was to analyze the cultivable oral microbiota of patients with obstructive sleep apnea (OSA) and its association with the periodontal condition. Methods The epidemiology profile of patients and their clinical oral characteristics were determined. The microbiota was collected from saliva, subgingival plaque, and gingival sulcus of 93 patients classified into four groups according to the periodontal and clinical diagnosis: Group 1 (n = 25), healthy patients; Group 2 (n = 17), patients with periodontitis and without OSA; Group 3 (n = 19), patients with OSA and without periodontitis; and Group 4 (n = 32), patients with periodontitis and OSA. Microbiological samples were cultured, classified, characterized macroscopically and microscopically, and identified by MALDI-TOF-MS. The distribution of complexes and categories of microorganisms and correlations were established for inter- and intra-group of patients and statistically evaluated using the Spearman r test (p-value <0.5) and a multidimensional grouping analysis. Result There was no evidence between the severity of OSA and periodontitis (p = 0.2813). However, there is a relationship between the stage of periodontitis and OSA (p = 0.0157), with stage III periodontitis being the one with the highest presence in patients with severe OSA (prevalence of 75%; p = 0.0157), with more cases in men. The greatest distribution of the complexes and categories was found in oral samples of patients with periodontitis and OSA (Group 4 P-OSA); even Candida spp. were more prevalent in these patients. Periodontitis and OSA are associated with comorbidities and oral conditions, and the microorganisms of the orange and red complexes participate in this association. The formation of the dysbiotic biofilm was mainly related to the presence of these complexes in association with Candida spp. Conclusion Periodontopathogenic bacteria of the orange complex, such as Prevotella melaninogenica, and the yeast Candida albicans, altered the cultivable oral microbiota of patients with periodontitis and OSA in terms of diversity, possibly increasing the severity of periodontal disease. The link between yeasts and periodontopathogenic bacteria could help explain why people with severe OSA have such a high risk of stage III periodontitis. Antimicrobial approaches for treating periodontitis in individuals with OSA could be investigated in vitro using polymicrobial biofilms, according to our findings.